Pharmacologic inhibition of hepcidin expression reverses anemia of chronic inflammation in rats - Theurl, Igor (American Society of Hematology, 2011)
Anemia of chronic inflammation (ACI) is the most frequent anemia in hospitalized patients and is associated with significant morbidity. A major underlying mechanism of ACI is the retention of iron within cells of the reticuloendothelial system (RES), thus making the metal unavailable for efficient erythropoiesis. This reticuloendothelial iron sequestration is primarily mediated by excess levels of the iron regulatory peptide hepcidin down-regulating the functional expression of the only known cellular iron export protein ferroportin resulting in blockade of iron egress from these cells. Using a well-established rat model of ACI, we herein provide novel evidence for effective treatment of ACI by blocking endogenous hepcidin production using the small molecule dorsomorphin derivative LDN-193189 or the protein soluble hemojuvelin-Fc (HJV.Fc) to inhibit bone morphogenetic protein-Smad mediated signaling required for effective hepcidin transcription. Pharmacologic inhibition of hepcidin expression results in mobilization of iron from the RES, stimulation of erythropoiesis and correction of anemia. Thus, hepcidin lowering agents are a promising new class of pharmacologic drugs to effectively combat ACI.